Long-term effects of a 12 weeks high-intensity functional exercise program on physical function and mental health in nursing home residents with dementia: a single blinded randomized controlled trial - Telenius, Elisabeth Wiken (BMC Geriatr, 2015)
BACKGROUND: Research indicates that exercise can have a positive effect on both physical and mental health in nursing home patients with dementia, however the lasting effect is rarely studied. In a previously published article we investigated the immediate effect of a 12 weeks functional exercise program on physical function and mental health in nursing home residents with dementia. In this paper we studied the long-term effect of this exercise program. We explored the differences between the exercise and control group from baseline to 6 months follow-up and during the detraining period from month 3 to 6. METHODS: A single blind, randomized controlled trial was conducted and a total of 170 nursing home residents with dementia were included. The participants were randomly allocated to an intervention (n = 87) or a control group (n = 83). The intervention consisted of intensive strengthening and balance exercises in small groups twice a week for 12 weeks. The control condition was leisure activities. Thirty participants were lost between baseline and six-month follow-up. Linear mixed model analyses for repeated measurements were used to investigate the effect of exercise after detraining period. RESULTS: The exercise group improved their scores on Berg Balance Scale from baseline to 6 months follow-up by 2.7 points in average. The control group deteriorated in the same period and the difference between groups was statistically significant (p = 0.031). The exercise group also scored better on NPI agitation sub-score after 6 months (p = 0.045). CONCLUSION: The results demonstrate long-time positive effects of a high intensity functional exercise program on balance and indicate a positive effect on agitation, after an intervention period of 12 weeks followed by a detraining period of 12 weeks. Identifier at ClinicalTrials.gov: NCT02262104